Stress Granules Modulate SYK to Cause Tau-Associated Neurocognitive Deterioration in 5XFAD Mouse After Anesthesia and Surgery - Shen, Yang; Zhang, Tong; Zhang, Yinglin; Wang, Yinuo; Yao, Junyan (Frontiers in Aging Neuroscience, 2021)
Background: Alzheimer’s disease (AD) is the most common types of dementia. However, no curative therapy has been found effective to slow down the process of AD. It is reported that anesthesia and surgery will induce neurocognitive deterioration in Alzheimer’s disease, but the mechanism is not quite clear. In this study, we aim to compare the cognitive impairment between 5XFAD transgenic (Tg) mice and its littermates (LM) mice after isoflurane anesthesia and surgery in order to clarify the specific impacts of anesthesia and surgery on AD individuals and to explore the mechanisms. Methods: We performed abdominal surgery in cognitively impaired, 4-month 5XFAD Tg mice and LM control mice. Isoflurane anesthesia (1.4%) was induced over 2h. Open field and Fear conditioning tests were conducted 1, 3, 7 days after anesthesia/surgery. The total distance, velocity and freezing time were the major outcomes. P-tau (AT8), tau oligomers (T22), stress granules (SGs), the SYK tyrosine kinase and p-SYK in the hippocampus at postoperative day 1 were evaluated by Western Blot assays. The colocalization of SGs, SYK, p-SYK and neurons in hippocampus section were assessed using qualitative immunofluorescence. Results: In Open field test, no difference between the distance and velocity of LM mice and 5XFAD Tg mice was found at 1 day after anesthesia/surgery. 5XFAD Tg mice exhibited reduced freezing time of Fear conditioning context test at postoperative day 3, but not at day 7; The LM mice showed no changes in Fear conditioning tests. More p-tau, tau oligomers, SGs, SYK and p-SYK were evident in the hippocampus region of 5XFAD Tg mice at postoperative day 1. In addition, SGs, SYK, p-SYK were colocalized with hippocampus neurons. Conclusions: This study demonstrates that anesthesia and surgery may induce the tau-associated neurocognitive deterioration in AD individuals. The mechanism under it may be associated with SGs and the tyrosine kinase, SYK. After anesthesia and surgery, in 5XFAD Tg mice, SGs were formed and SYK was phosphorylated, which may be contributed to the phosphorylation of tau protein. Our present study provided hints that AD individuals may be more vulnerable to anesthesia and surgery.